2016
DOI: 10.1272/jnms.83.93
|View full text |Cite
|
Sign up to set email alerts
|

Right Inguinal Hernia Encompassing the Uterus, Right Ovary and Fallopian Tube in an Elderly Female: Case Report

Abstract: The uterus, ovary, and fallopian tube are rarely present in an inguinal hernia. We report on an operation to treat just such a rare condition for a right inguinal hernia. An 87-year-old Japanese woman was admitted with swelling in the right inguinal region and a purulent discharge from the vagina. Vital signs were stable, but the mobile mass was irreducible. Computed tomography of the abdomen indicated uterine tissue in a right inguinal hernia. We diagnosed an inguinal hernia with an incarcerated uterus and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
4
0
3
Order By: Relevance
“…19 Consequently, 15 papers (13 case reports, 2 case series), comprising 17 patients with ovarian inguinal hernias, were included in our review. 5,6,[20][21][22][23][24][25][26][27][28][29][30][31][32] summarised in Tables 1-3. The mean patient age was 47.9 years (standard deviation: 23.7 years) and over half of the patients (n=9, 56%) were women of reproductive age (18-45 years).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Consequently, 15 papers (13 case reports, 2 case series), comprising 17 patients with ovarian inguinal hernias, were included in our review. 5,6,[20][21][22][23][24][25][26][27][28][29][30][31][32] summarised in Tables 1-3. The mean patient age was 47.9 years (standard deviation: 23.7 years) and over half of the patients (n=9, 56%) were women of reproductive age (18-45 years).…”
Section: Resultsmentioning
confidence: 99%
“…Data concerning follow-up were recorded by Ueda et al, Malik et al and Ray et al, who detected no hernia recurrence in the operated patients at nine months, three months and six weeks following surgery respectively. 27,28,30…”
Section: Resultsmentioning
confidence: 99%
“…Evaluando una revisión bibliográfica, Ueda et al 12 , del año 2016, sumado a nuevos de casos publicado en PubMed, hasta mayo de 2020, se encontraron 13 casos de hernia útero inguinal en mujeres en edad reproductiva [12][13][14][15] ; dentro de los cuales, en 10 casos, el contenido de saco herniario conservaba un útero rudimentario, un útero normal fue encontrado en 2 de los 13 casos. La edad promedio de presentación fue de 37,4 años, en 4 casos reportados las pacientes eran mayores de 40 años.…”
Section: Discussionunclassified
“…Furthermore, some literatures reported inguinal herniation of ovary with or without fallopian tube and uterus into the inguinal canal regardless of congenital genitourinary syndromes. Such as Daib et al, 2017 reported a 1-month year old infant with utero-ovarian herniation into left inguinal canal [2] and another study by Ueda et al,2016 indicated the inguinal herniation of uterus, ovary and fallopian tube in an old woman [9].…”
Section: Discussionmentioning
confidence: 99%